Histone Deacetylase 1 Plays an Acetylation-Independent Role in Influenza A Virus Replication - Chen, Lin; Wang, Chengmin; Luo, Jing; Su, Wen; Li, Meng; Zhao, Na; Lyu, Wenting; Attaran, Hamidreza; He, Yapeng; Ding, Hua; He, Hongxuan (Frontiers in Immunology, 2017)
Influenza A viruses (IAVs) take advantage of the host acetylation system for their own benefit. Whether the nucleoprotein (NP) of influenza A viruses undergoes acetylation and the interaction between the nucleoprotein and the class Ⅰ histone deacetylases were largely unknown. Here, we showed that the NP protein of IAV interacted with histone deacetylase 1 (HDAC1), which down-regulated the acetylation level of NP. Using mass spectrometry, we identified lysine 103(K103) as an acetylation site of the NP. Compared with wild-type protein, two K103 NP mutants, K103A and K103R, enhanced replication efficiency of the recombinant viruses in vitro. We further demonstrated that HDAC1 facilitated viral replication via two paths: promoting the nuclear retention of NP and inhibiting TBK1-IRF3 pathway. Our results lead to a new mechanism for regulating NP acetylation, indicating that HDAC1 may be a possible target for antiviral drugs.